The Phenomenon of "Burnout" Among PGSD Students; Perspectives on Social Skills in the Post-Pandemic Era of Covid-19 - Fitriyani Fitriyani; Anna Maria Oktaviani (International Journal of Science and Applied Science: Conference Series, 2022)
The background of the problems in this study is based on the problems that occur today where lectures are often identified with the existing busyness, be it busyness in the campus environment or outside the campus. Burnout is triggered as a result of stress that is not resolved, causing loss of enthusiasm, decreased performance in learning, and even a decrease in the desire to interact or socialize with people around it,  so that it leads to a condition where a person will withdraw from the environment. There are three aspects to burnout, namely emotional fatigue, depersonalization, and low self-esteem. The purpose of this study is (1) To find out an overview of burnout that occurs among students, especially PGSD study programs (2) To find out the magnitude of the influence caused by high burnout rates on student learning motivation. This type of research is a qualitative research involving the subjects in this study are as many as 15 students of the Elementary School Teacher Education Study Program at Pelita Bangsa University, located in Cikarang and at the Jakarta State University. The approach is carried out using the case study method. Emotional fatigue in students is characterized by feeling tired and not being excited in doing assignments. When experiencing burnout, a person's emotional state becomes unstable, such as irritability, despair, and cynicism. Emotional fatigue results in the draining of a person's emotional source which will then interfere with his mental state and even his physical health.